Endoscopic Ultrasound-Guided Vascular Therapy for Portoduodenal Fistula - Tanyaporn Chantarojanasiri; Apichet Sirinawasatien; Chalermrat Bunchorntavakul; Aroon Siripun; Sa-ard Treepongkaruna; Thawee Ratanachu-ek (Korean Society of Gastrointestinal Endoscopy, 2020)
Portoenteric fistula is a rare cause of massive upper gastrointestinal bleeding. Most cases can be treated with radiointervention or surgery, but portoenteric fistula is associated with a high mortality. We reported a case of intermittent massive upper gastrointestinal bleeding in a 33-year-old man with cholangiocarcinoma who underwent surgical resection followed by chemoradiation. A portoduodenal fistula due to chronic duodenal ulceration was identified. The bleeding was successfully controlled by endoscopic ultrasound-guided coil placement through the duodenal bulb using the anchoring technique. Follow-up endoscopy and computed tomography scan showed multiple coil placements between a part of the portal vein and the duodenal bulb without any evidence of portal vein thrombosis. There were no complications, and bleeding did not recur during the 8-month follow-up period.